Adverse selection and the performance of private equity co-investments - Braun, R; Jenkinson, T; Schemmerl, C (Elsevier, 2019)
Investors increasingly look for private equity managers to provide opportunities for co-investing outside the fund structure, thereby saving fees and carried interest payments. In this paper, we use a large sample of buyout and venture capital co-investments to test how such deals compare with the remaining fund investments. In contrast to Fang, Ivashina, and Lerner (2015), we find no evidence of adverse selection. Gross return distributions of co-investments and other deals are similar. Co-investments generally have lower costs to investors. We simulate net returns to investors and demonstrate how reasonably sized portfolios of co-investments significantly outperform fund returns.